2020
DOI: 10.1002/smll.201906435
|View full text |Cite|
|
Sign up to set email alerts
|

Controlling the Facet of ZnO during Wet Chemical Etching Its (0001¯) O‐Terminated Surface

Abstract: Special surface plays a crucial role in nature as well as in industry. Here, the surface morphology evolution of ZnO during wet etching is studied by in situ liquid cell transmission electron microscopy and ex situ wet chemical etching. Many hillocks are observed on the (000 1) O-terminated surface of ZnO nano/micro belts during in situ etching. Nanoparticles on the apex of the hillocks are observed to be essential for the formation of the hillocks, providing direct experimental evidence of the micromasking me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…13 Sun et al have studied the hillocks formed on the (0001̄) O-terminated surface of ZnO nano/micro belts during in situ etching, and found that the surfaces of the hillocks are {011̄3̄} crystal facets instead of {011̄1̄} crystal facets due to the O 2 plasma pretreatment before the in situ experiments. 44 As the Zn-terminated polar plane is less stable in O-rich conditions caused by O 2 plasma treatment, 43,45 {011̄3̄} semi-polar planes are formed. 44 In the present study, the etching of the (0001̄) O-terminated end of the ZnO nanowire also shows a similar phenomenon to that in the ZnO nano/micro belts reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…13 Sun et al have studied the hillocks formed on the (0001̄) O-terminated surface of ZnO nano/micro belts during in situ etching, and found that the surfaces of the hillocks are {011̄3̄} crystal facets instead of {011̄1̄} crystal facets due to the O 2 plasma pretreatment before the in situ experiments. 44 As the Zn-terminated polar plane is less stable in O-rich conditions caused by O 2 plasma treatment, 43,45 {011̄3̄} semi-polar planes are formed. 44 In the present study, the etching of the (0001̄) O-terminated end of the ZnO nanowire also shows a similar phenomenon to that in the ZnO nano/micro belts reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…The different factors will have different influence on the properties. [47,48] Through the use of the k•p perturbation approach [49][50][51][52] and deformation potential theory [53] (See details in the Supporting Information), we calculated the biaxial strain effect on the light emission spectra of In x Ga 1−x N. Since the strain components vary depending on which crystal plane the InGaN was grown, three light emission wavelength evolution graphs along with different In concentrations of In x Ga 1-x N grown on (0221), (0111), and (0112) planes are presented in Figure 4a and Figure S8, Supporting Information. The detailed strain components and bandgap changes brought by these biaxial stresses for different In x Ga 1−x N compounds with various In content x are summarized in Table S1, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…For in situ liquid cell TEM, different water environments (such as neutral, acid, or alkaline environments) have an essential impact on the etching reaction pathway. [38,[53][54][55][56][57][58][59][60][61][62] These studies have proved that the electron beam could introduce reactive agents and even trigger reactions, significantly etching reactions in water, which produced various radical products (such as OH•, H 2 O 2 , HO 2 •, H•, H 3 O + , H 2, and O 2, etc.). Such as, the cubic CeO 2 nanoparticle transforms into the hexagonal Ce 2 O 3 nanoparticle during the dissolution process in Figure 3A.…”
Section: Radical Productsmentioning
confidence: 99%
“…Reproduced with permission. [59] Copyright 2022, Wiley-VCH. E) Observing the etching process of Au nanorod in the presence of O 2 gas nanobubbles in HBr solution.…”
Section: Radical Productsmentioning
confidence: 99%
See 1 more Smart Citation